การศึกษาความสัมพันธ์ระหว่างการใช้งานกับต้นทุนการดำเนินการของเครื่องจักรก่อสร้าง - พีรพล เพ็ชรตระกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research explores the relationship between the actual usages of construction machines and their operation costs. A simulation model to predict the operating cost of heavy equipment for earth work construction is also introduced based on such relationship. In this research, as a source of data collection, construction equipment with two different usage meters, which are distance meters and hourly meters, are represented by the 21-metric-ton trucks and 20-ton hydraulic excavators with 0.7 cubic-meter buckets, respectively. Questionnaires were distributed to 38 experienced contractors to identify the structure of equipment operating cost and also the factors affecting the equipment operating costs. Three specialists were also interviewed to evaluate the factors for developing the simulation model. Fuel consumption, lubricant usages, and maintenance cost of the equipment were collected on 23 trucks and 17 hydraulic excavators from 3 main contractors. The data available for analysis came from historical equipment records between 1998 and 2006. The simulation model was generated from the site operation conditions as independent variables and the fuel consumption, lubricant usage as well as percentages of cumulative maintenance cost of equipment. The multiple regression analysis was used to identify the relationships of these variables. The errors found from the prediction of fuel consumption were up to 10 percents and 8 percents for trucks and hydraulic excavators, respectively. In addition, from estimating the lubricant costs, the maximum errors were up to 30 percents for both equipment with distance meters and hourly meters. From the research, it was found that the fuel consumptions varied due to the factors related to the work conditions whereas the lubricant consumptions and percentages of cumulative maintenance costs varied relatively to the usage meters of equipment.